2017
DOI: 10.7196/sajch.2017.v11i2.1167
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for cranial ultrasound abnormalities in very-low-birth-weight infants at Charlotte Maxeke Johannesburg Academic Hospital

Abstract: Background. Periventricular-intraventricular haemorrhage (IVH) and cystic periventricular leukomalacia (cPVL) contribute to neonatal mortality and morbidity. Low birth weight and gestational age are among the risk factors for IVH and cPVL. Objectives. To assess how many very low birth weight (VLBW) infants had cranial ultrasound screening at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) and to determine the prevalence of cranial ultrasound abnormalities. To compare the characteristics and risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…The most prevalent cause of death in the study was IVH. This showed similarity with the findings of Ghoor et al 18 The research done by Ballabh 19 and Mulindwa et al 20 reported that the probability of developing IVH increased in cases of birth asphyxia, sepsis, mechanical ventilation, and patent ductus arteriosus. They also observed a higher rate of mortality amongst the neonates who developed IVH.…”
Section: Discussionsupporting
confidence: 90%
“…The most prevalent cause of death in the study was IVH. This showed similarity with the findings of Ghoor et al 18 The research done by Ballabh 19 and Mulindwa et al 20 reported that the probability of developing IVH increased in cases of birth asphyxia, sepsis, mechanical ventilation, and patent ductus arteriosus. They also observed a higher rate of mortality amongst the neonates who developed IVH.…”
Section: Discussionsupporting
confidence: 90%
“…In Uganda, a prospective study on infants GA <32 weeks reported 14/41 (32%) any IVH and 8/41 (20%) sIVH 34. Three studies from South Africa reported 15%–27% any IVH and 5%–8% sIVH in infants ≤1500 g 35–37. Most of these rates are comparable with our estimates, which suggests that at these select institutions, risk may be similar to those in high-income countries.…”
Section: Discussionsupporting
confidence: 82%